ATTRIBUTE DATA MODELS: ATTRIBUTE DATA MODELS - Ivanov, Sabin (JOURNAL SCIENTIFIC AND APPLIED RESEARCH, 2025)
The article discusses non-spatial data called attributes. Each geographical object or phenomenon possesses one or more attributes that define it, describe it or represent it. The attribute can be size, density, name, date, or population.